When PCOS isn’t the answer: Müllerian para-ovarian cyst presenting with hyperandrogenism - Rezwana, Israt; Hasan, Mahmudul; Islam, AKM Aminul (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Hyperandrogenism in women is most commonly caused by polycystic ovary syndrome (PCOS), congenital adrenal hyperplasia (CAH), or androgen-secreting ovarian/adrenal tumors. Para-ovarian (para-tubal) cysts are generally benign and hormonally silent. A 42-year-old obese (BMI 35Kg/m2) woman presented with progressive hirsutism and amenorrhea for 5 years. Biochemistry revealed elevated total testosterone 4.66 nmol/L [normal: 0.38-1.97 nmol/L]. Adrenal imaging, 17-hydroxyprogesterone, and DHEA-S were normal. Trans vaginal USG reported polycystic ovaries along with a right adnexal cyst [9.3x6.5cm]. MRI revealed a right adnexal ovarian cyst along with bilateral ovarian hyperplasia. The patient underwent laparoscopic cystectomy. Post-operatively, serum testosterone dropped markedly to 1.13 nmol/L without any anti-androgen medication, and clinical symptoms improved, evidenced by resumption of menstruation and improvement of hirsutism. Histopathology confirmed a Müllerian cyst with no evidence of neoplasia. Although para-ovarian cysts are typically non-functional, rare reports suggest possible androgen production or paracrine ovarian stromal stimulation due to cystic lesions. In our case, normalization of testosterone following cystectomy strongly supports a causal relationship. Potential mechanisms include stromal luteinization within the cyst wall or stimulation of adjacent ovarian tissue. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S58]